(Invited) Multifunctional Technology with Monolithic Integrated THz-, Photonic- and µ-Fluidic Modules. (14th September 2015) - Mai, Andreas; Lischke, Stefan; Wietstruck, Matthias; Zimmermann, Lars; Kaynak, Mehmet; Tillack, Bernd
Abstract : In this paper we present a multifunctional technology platform with different monolithic integrated modules like THz devices, i.e. complementary SiGe heterojunction bipolar transistors, silicon photonics components in particular Ge-PIN photo detectors and finally the wafer-level integration of µ-fluidic channels for sensor applications. Challenges during the monolithic integration of these different modules were reviewed and necessary process adaptations discussed in order to enable a co-integration.